The Effect of Twisted Polymer Fiber on Physical and Mechanical Characteristics of Concrete C35 - Mirzaei, Reza; Zarifmoghaddam, Naser (Journal of the Institute of Engineering, 2018)
Concrete as the most used material, is known as an integral part of construction. So far, many studies have been done in the field of improving the quality of concrete that most of them have examined change in concrete mix which is called concrete mix plan. However, the use of additives and also replacing commonly used materials in concrete with new materials always has been noteworthy. In this study, description of tests that have been done on fiber reinforced concrete will be discussed. Also, the condition of concrete mix plan will be discussed. Comparison between results of the tests showed that Forta reinforced concretes have more compressive, flexural and tensile strength and modulus of elasticity than normal and ordinary concretes. Journal of the Institute of Engineering, 2018, 14(1): 126-135